2020
DOI: 10.2147/cmar.s253591
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Hydroxytyrosol on Expression of Apoptotic Genes and Activity of Antioxidant Enzymes in LS180 Cells</p>

Abstract: Purpose: Colorectal cancer is the third-most commonly occurring cancer in developed countries. Hydroxytyrosol is a potent antioxidant that has several activities, such as oxidative-stress control, inhibition of cell proliferation, and induction of apoptosis. In this study, the effect of hydroxytyrosol on the expression of genes effective in apoptosis-BAX, BCL2, CASP3, P53, PPARG, and NFE2L2-and antioxidant-enzyme activity in LS180 cells of human colorectal cancer was investigated. Methods: The human colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The extracts were indeed capable of dose-dependently counteracting H 2 O 2 -induced cell death and restoring cell viability completely at the dosages of 50 and 100 µg/mL. Our current findings support and confirm previously performed experiments; indeed, similarly to EVOO-contained phenolic compounds [ 9 , 10 , 45 , 46 , 50 ], olive oil processing byproducts such as OMW are a source of valuable compounds harboring health benefit properties.…”
Section: Discussionsupporting
confidence: 90%
“…The extracts were indeed capable of dose-dependently counteracting H 2 O 2 -induced cell death and restoring cell viability completely at the dosages of 50 and 100 µg/mL. Our current findings support and confirm previously performed experiments; indeed, similarly to EVOO-contained phenolic compounds [ 9 , 10 , 45 , 46 , 50 ], olive oil processing byproducts such as OMW are a source of valuable compounds harboring health benefit properties.…”
Section: Discussionsupporting
confidence: 90%
“…Natural antioxidants derived from medicinal plants are composed of polyphenols (including phenolic acids and flavonoids), carotenoids and vitamins [10]. These natural antioxidants are recognized for their ability to scavenge reactive oxygen species (ROS) [11][12][13]. Oxidative stress is a harmful event that is responsible for development of a wide range of disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all compounds showed the ability to inhibit cell proliferation and induce apoptosis, although with different targets, depending on the tumor model. Secoiridoids inhibit essential pathways for proliferation, such as AKT and ERK [ 78 , 79 , 80 , 81 , 92 , 106 , 107 , 122 ], induce apoptosis by interfering with the expression of pro-apoptotic proteins, such as Bax [ 97 ], or anti-apoptotic Mcl1 and Bcl-xl proteins [ 79 ], modulate the autophagy pathway [ 83 , 103 , 104 , 126 ], and regulate metalloproteinases [ 79 ]. The action that they perform on the basic mechanisms of EMT, which results in tumor invasiveness and metastasis, is also relevant.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hormozi et al demonstrated that HTyr treatment of human CRC LS180 cells induced the expression of pro-apoptotic genes, such as CASP3 and Bax , and increased antioxidant enzyme activity, leading to a reduction of tumor cell proliferation [ 97 ].…”
Section: Tyrosol and Hydroxytyrosolmentioning
confidence: 99%